Governing Water, Engaging Community: Indonesian Water Security Roadmap - Ida Widianingsih; Riswanda Riswanda; Caroline Paskarina (Journal of Governance, 2020)
Water policy assessment could be multifaceted in nature considering its systemic implications for governance. The context of governing water is constantly changing. Water demand may rise of population growth and economic activities, whilst water service provision may be challenging due to interconnected aspects of water justice, water conflict and water resources management.  Policymaking adaptability to change should think about the consequences of the policy design to all stakeholders, including their situation and options and determine the most possible alternative resolutions. Most attention is given to key lessons for development considering the impact of and the need to discuss the issue of water security in a way that could contribute to protecting lives and the environment. To some extent the issue of water security in Indonesia is interconnected with general enabling measures of assessing the existing regulation at the national level. Unambiguous actions may be required at regional and local levels, together with sound socio-economic and socio-cultural institutions and instruments, namely building capacity and advocating partnerships. This primary qualitative research is about providing water security roadmap in West Java as a case in point, contributing to policy discourse on how to govern the complexity of water security issue concerning making model grounded on collaborating local community participation and regional government support.